The Influence of Cooperative Integrated Reading and Composition (CIRC) Learning Strategies on the Learning Outcomes of Islamic Cultural History of Students Madrasah Aliyah in Private - Telaumbanua, Nuril Meylani; Arsyad, Junaidi; Zein, Achyar (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
Cooperative Integrated Reading and Composition is one strategy for learning Islamic Cultural History (CIRC). The use of CIRC learning in Islamic Cultural History learning provides students with direct experience; the goal is to foster students to develop cognitive, affective, and psychomotor aspects of students as a whole, as well as interact with friends and their environment. A quasi-experimental method was used in this study. This method was chosen because the treatment class for both cooperative integrated reading and composition (CIRC) learning and expository learning classes is pre-formed, and the controlled student characteristics are independent learning. The population and sample in this study were used in a 2 x 2 factorial research design. According to the findings of the study, there were differences in the learning outcomes of Islamic Cultural History between students who were taught using the CIRC learning strategy and those who were taught using the expository learning strategy. higher than the average learning outcomes of Islamic Cultural History students taught using expository learning strategies at the Private Madrasah Aliyah in Gunungsitoli City (= 27.00).